(untitled) (REMUNOM, 2025)
The golden trumpet tree is commonly used in urban landscaping, Agroforestry Systems, and reforestation of degraded areas. The areca bamboo palm, one of the most popular palms in the world, is widely used in landscaping and interior decoration. Despite the widespread recognition of these species, there is a lack of information regarding their phytosanitary aspects. This study aims to report the association of defoliating caterpillars with the golden trumpet tree and areca bamboo palm in Rio Branco, Acre, Brazil. In July 2024, the occurrence of caterpillars was observed on the leaves and trunk of the golden trumpet tree and the leaflets of the areca bamboo palm, both cultivated in a residential urban garden in the municipality of Rio Branco, Acre. The caterpillars were collected, placed in a perforated-lid container, and transported to the Entomology Laboratory of Embrapa Acre. In the laboratory, they were identified at the genus level under a stereoscopic microscope with the aid of specialized literature. The caterpillars associated with the golden trumpet tree were identified as belonging to the genus Acharia (= Sibine), while those associated with the areca bamboo palm were identified as belonging to the genus Opsiphanes. This study provides the first records of the association of Acharia sp. and Opsiphanes sp. with the golden trumpet tree and areca bamboo palm, respectively.